(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines analytical thinking as a central psychological-pedagogical category within the field of neuropedagogy. It nalyses the neurobiological mechanisms underlying analytical cognitive activity—specifically, the roles of the prefrontal cortex, executive functions, working memory, and inhibitory control. The psychological structure of analytical thinking is investigated in relation to pedagogical practice. The principles of neuropedagogical design for the educational process—aimed at fostering students’ analytical abilities—are discussed. It is demonstrated that the neuropedagogical approach provides a scientific basis for substantiating and refining pedagogical strategies for developing analytical thinking, grounded in scientific data regarding brain function.